The European Union towards freedom of speech in Vietnam – in the context of the protection of human rights in 2012-2023 - Serwatka, Andżelika (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
Freedom of speech, independent media, and the protection of human rights are integral foundations of democratic society, as well as values that the European Union has been promoting and strengthening in countries around the world for years. One such country is Vietnam - a state with one of the highest rates of violations of freedom of speech, press, and media. Hence, Vietnamese-EU relations appear to be interesting, especially when considering economic issues as well. The aim of this chapter is to present how EU actions to promote human rights, particularly increasing freedom of speech, in Vietnam are linked to the economic component. By presenting the history of Vietnamese-EU relations, economic agreements, and their impact on freedom of speech in Vietnam, it will be possible to address questions regarding issues such as the problem of protecting freedom of speech in Vietnam, the EU's engagement and initiatives for human rights protection in Vietnam, and the non-economic effects of EU-Vietnamese trade agreements.